Reading the family: A constructivist grounded theory on organ donation conversations. - Lissette Avilés (PLoS ONE)
Approaching families to discuss deceased organ donation authorisation is considered one of the central stages of the organ donation process. In many countries, specialist nurses lead the organ donation process, approach and support families. However, how these encounters occur is not yet fully understood. A constructivist grounded theory methodology was used to conceptualise the process of approaching families from the perspectives of healthcare professionals and families. Data collected included six months of observations across two large hospitals in Chile, documents, interviews and focus groups with 71 participants including healthcare professionals involved in the organ donation process, and bereaved families who were approached for organ donation conversations. The theory Reading the family was developed to explain the relational process of how nurse organ donor coordinators approach families to negotiate organ donation authorization. It explains the sophisticated and skilled process of accessing, assessing and managing family's emotions to negotiate organ donation authorization as a family unit. The theory has two dimensions, indirect and direct, which refers to when and how nurses read families emotions to lead organ donation conversations and support bereaved families' decision-making process. These dimensions critically depend on the clinicians set of beliefs and communication processes. Understanding the complexities of approaching families is essential for practice and policymaking, particularly when there is a trend towards individual decision-making instead of understanding organ donation as a family affair. Reading the family could be eventually applied in other contexts and situations that involve navigating difficult conversations, and therefore, further research is needed and suggested to assess the feasibility of its application.